Design Thinking Perancangan Infused Water Inspirasi Al-Qur’an dan Hadis dalam Pemulihan Kesehatan Lansia Penyintas Covid-19 - Wahyudin Darmalaksana; Safra Ulya; Hidayatul Fikra; Susanti Vera (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the inspiration of the Qur'an and hadith in the design of infused water for the restoration of the health of the elderly Covid-19 survivors. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is design thinking. While the object of this research material is the inspiration of the Qur'an and hadith about infused water. The context of this research is the recovery of the health of elderly Covid-19 survivors. The results of the research and discussion show that the Qur'an emphasizes a healthy lifestyle and encourages humans to consume good foods such as dates, while the hadith teaches the making of nabiz in the form of water soaked in dates. The content of this sacred text became the inspiration for designing infused water for the recovery of the health of elderly Covid-19 survivors. The conclusion of this study is that the inspiration of the Holy Qur'an and Hadith texts in designing infused water with design thinking procedures has resulted in benefits for the recovery of the health of elderly Covid-19 survivors.